Fabrication and characterization of zein nanofibers integrated with gold nanospheres. (1st February 2022) - Cetinkaya, Turgay; Wijaya, Wahyu; Altay, Filiz; Ceylan, Zafer
Abstract: The synthesis, characterization, and coating effect of zein nanofibers integrated with gold nanospheres were studied. Zein solution including ethanol/liquid gold nanospheres (80/20 v/v) was prepared to produce complex nanofibers. Dielectric constant (ε′), dielectric loss factor (ε′′), and loss tangent (ε′′/ε′) values of feed solutions were evaluated at 300 and 3000 MHz, and electrical conductivity was measured (808.67 ± 2.082 μs/cm). SEM image showed a bead free structure of the gold-zein complex. Zeta potential and DLS measurements (translational diffusion coefficient, hydrodynamic radii, polydispersity index, major axis) were done by dispersing nanofibers in ethanol or water. The stability of nanofiber dispersed in ethanol was higher (+41.73 mV) compared to that of dispersed in water (+5.1 mV). Molecular characterization by FTIR confirmed the formation of the zein-gold complex through a nitrogen-gold coordination bond and electrostatic interactions. The gold-zein nanofibers coating in sea bream fillets reduced 17.8% of total mesophilic bacteria (TMAB) compared to the uncoated group (p < 0.05) after 8 days of observation. The highest changes in ε′ for uncoated (57.65%) and coated samples (14.84%) during storage showed the positive impact of nanofiber treatment. These results showed that zein nanofibers with gold nanospheres could be potentially used as antimicrobial layer for food products. Graphical abstract: Preparation, characterization, and surface coating of zein nanofibers integrated with gold nanospheres. Image 1 Highlights: Electrospinnability was affected by electrical conductivity and dielectric values. Binding between gold ion and zein molecules was confirmed by FTIR. Zein-gold nanofiber stability was studied by zeta potential measurements. Aggregation behavior of nanofiber in solutions was determined. The dielectric stability increased after treatment with zein-gold nanofibers.